Tribo-surface characteristics of Al-B4C and Al-SiC composites worn under different contact pressures - Shorowordi, Kazi Md; Haseeb, A.S. Md. Abdul; Celis, Jean Pierre (Elsevier, 2006)
Tribo-surface characteristics of two aluminium metal matrix composites (Al-MMC) of compositions Al-13 volB4C and Al-13 volSiC sliding against a commercial phenolic brake pad have been investigated under dry conditions. The wear tests were carried out using a pin-on-disc type apparatus at a linear speed of 1.62 ms(-1) under contact pressures ranging from 0.75 to 3.00 MPa. The coefficient of friction was recorded on line. Wear rates were calculated from mass loss measurements. Scanning electron microscope equipped with energy dispersive X-ray spectroscopy was used to examine the tribo-surface. It is found that wear rate of both composites increases with increasing contact pressure which is accompanied by increased roughness of Al-MMC tribo-surface. The friction coefficient decreases slightly at high contact pressure. The wear rate and friction coefficient of Al-B4C are lower than that of Al-SiC. A transfer layer consisting mostly of the constituents of the phenolic counterbody is observed on Al-MMC pins. The characteristics and role of the transfer layer, whose tribochemistry is dependent upon contact pressures, are discussed. (c) 2006 Elsevier B.V All rights reserved.